Stressors, psychological states, and relationship quality among East Malaysian adults with partners amid the COVID-19 lockdown - Jasmine Adela Mutang; Chua, Bee Seok; Hon, Kai Yee; Siau, Ching Sin; Walton Wider; Rosnah Ismail (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The COVID-19 pandemic has had a huge impact not only on healthcare systems and economic threats but also on relationships. Due to the massive measures of the Movement Control Order, such as social distancing, strictly limited physical activities, and making adjustments to working from home—merged with the pandemic’s fear—romantic partners may face challenges that affect the quality of their relationships. The purpose of this study was to (i) identify stressors experienced by participants during the COVID-19 lockdown, (ii) evaluate participants’ psychological well-being before and during the lockdown, and (iii) see if participants’ perceived relationship quality differed before and during the lockdown. An online self-report questionnaire was used to recruit 334 adults (58.1 percent female, 41.9 percent male) with partners (married = 304, engaged = 12, and in committed relationships = 17). Participants were asked about stressors they encountered as a result of COVID-19 using an open-ended question. The Depression Anxiety Stress Scales (DASS-21) were used to assess mental health, and the Perceived Relationship Quality Component (PRQC) Inventory was used to assess relationship quality. According to the findings, the top three common stressors reported by participants were financial problems, restricted movement, and fear of COVID-19 infection. Participants reported significantly higher levels of stress, anxiety, and depression during the lockdown than before. The findings also revealed that participants’ relationship quality improved during the lockdown compared to before the lockdown. The current study contributes by providing information on the impact of the COVID-19 pandemic on mental health and the quality of couples’ relationships during the pandemic.